Lipid Composition of Three Different Types of Land Snails Consumed In Nigeria (Global Journal of Science Frontier Research, 2012)
The levels of fatty acids, phospholipids and zoosterols were determined in the edible parts of three land snails consumed in Nigeria [Archachatina marginata, Archatina (archatina) archatina and Limicolaria sp.)] on dry weight basis. Results showed crude fat varied from 2.22-2.38 g/100 g; SFA varied from 37.5-49.8 % of total fatty acids, total unsaturated fatty acids varied from 50.2-62.5 %, PUFA ranged from 25.5-38.7 %. In the phospholipids, phophatidylcholine was highest in all the samples with a range of 1.55-2.88 mg/100 g. Only cholesterol had results > 0.00 mg/100 g in the sterols with a value range of 37.1 -45.1 mg/100 g. Eicosadienoic acid (C20: 2 cis -11, 14) was the highest PUFA in all the samples with range values of 8.36-16.7 mg/100 g.
Keywords: lipid profiles; three land snails; consumed in nigeria